Impact of Transactional Leadership Style on Employee Job Satisfaction - Lumbantoruan, Sarinah; Kurniawan, Loviandi; Christi, Christi; Sihombing, Josua Bismark (TAZKIYA Journal of Psychology, 2020)
This research conducted to determine wether there is an influence of employee job satisfacation in terms of the transactional leadership style at UD. X in Medan. The hypotheses in this study is proposed that there is a positive influence in job satisfacation in terms of the transactional leadership style. On these study we used 105 people by using the saturated sample method. This research used quantitative research where the data collection uses a questionnaire. The assumptions test consisted of a normality test and a linearity test. The data analysis method uses the product moment correlation technique with the help of SPSS statistics 25 for Windows. The result showed that there was a significant influence between employee job satisfacation with transactional leadership style (Pearson Correlation 0.000, sig 0.000 < P= 0.05). The result of this study indicated that the contribution made by the transactional leadership style to job satisfaction is 81 percent. From the result of this study it can be concluded that research hyphothesis has a positive influence between transactional leadership style and job satisfaction.